History of the statue of Our Lady in Sejny - Kalinovskij, Jaroslav (Studia Teologiczne Białystok Drohiczyn Łomża, 2022)
Bearing in mind such an important presence of Mary in Christian worship, namely in the Catholic Church and Orthodoxy, as well as the popular piety (folk religiousness), it was undertaken to develop Marian themes in the sanctuary in Sejny, in the Ełk diocese. The subject of the study is: The cult of the Mother of God the sanctuary in Sejny. During this period, the cult developed, which made it possible to apply for the coronation of the figure, and the coronation itself certainly deepened this Marian part and gave rise to its continuation. The is devoted to the history of the Sejny parish and the history of the statue of the Mother of God. It needed a theological analysis, characteristic of the statue and presentation of the theological meaning. The is devoted to Marian popular piety. The Marian devotions practiced in the universal Church were presented, but, above all, those characteristics of the Sejny sanctuary, such as: the Perpetual Rosary, novena, chaplet and litany to Our Lady of Sejny, Holy Masses celebrated in Her honor and ordered by the faithful, sacraments and various pastoral initiatives being an expression of the vitality of the cult of the miraculous figure of Our Lady of Sejny.